CARDIAC SURGERYPenetrating cardiac injuries: 28-year data analysis - Jagelavicius, Zymantas; Budra, Mindaugas; Jovaisas, Vytautas; Kiskis, Gintaras; Kybartas, Algis; Zilinskas, Arunas; Liubertiene, Irena; Gruslys, Vygantas; Janilionis, Ricardas (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2013)
Background: Penetrating cardiac injuries are a dramatic and lethal form of trauma. They are usually sustained by young people. The majority of victims die before reaching the hospital. Aim of the study: The aim of the study was to establish prognostic criteria for the outcome of penetrating cardiac injury. Material and methods : We retrospectively reviewed the records of 186 patients with penetrating cardiac injuries who were operated on during the first 24 hours after admission. Results: The mean age was 33 (interquartile range (IQR): 26-44) years. 88.7% of victims were male. The mean time from the moment of trauma to arrival at the hospital in Vilnius city was 60 minutes (IQR: 50-91), whereas from the Vilnius region it was 240 (IQR: 82-390) minutes. The vast majority of patients (176/186, 94.6%) sustained stab wounds. Hemopericardium or cardiac tamponade (142/186, 76.3%) usually was found at the operation. Right ventricle was the most often injured heart chamber (75/186, 40.3%). Associated injuries were evaluated in 57.0% (106/186) of patients. The survival rate on discharge was 88.7%. Compared to non-survivors, the lucky patients had a higher systolic blood pressure on admission (94 mm Hg (IQR: 70-120) versus (vs.) 70 mm Hg (IQR: 0-80), p < 0.001). Survivors had all signs of life (SOL) more often (82.4% vs. 42.9%, p < 0.001), whereas more frequent findings in non-survivors were the following: tamponade (52.4% vs. 29.1%, p = 0.031), higher grade (IV-VI) of injury (90.5% vs. 29.7%, p < 0.001), injured right atrium (28.6% vs. 8.5% p = 0.014) or left ventricle (42.9% vs. 23.0%, p = 0.049) and an episode of heart arrest (85.7% vs. 7.9%, p < 0.001). Independent prognostic factors of survival were the presence of all SOL and younger age. Higher grade (IV-VI) of heart injury and heart arrest during surgery independently predicted mortality. Conclusions: According to our data, lower arterial blood pressure and absence of one or more SOL on admission, cardiac tamponade, higher grade injury, injured right atrium and asystole during operation are true precursors of fatal outcome.